2006
DOI: 10.1159/000092224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Placing a Clear Sealant on the Validity and Reproducibility of Occlusal Caries Detection by a Laser Fluorescence Device: An in vitro Study

Abstract: The principal aim of this in vitro study was to assess the validity and reproducibility of the detection of occlusal caries using laser fluorescence (LF), prior to and following the placement of a clear fissure sealant. It also aimed to compare the manufacturer’s standard cut-off recommendations with those published for in vitro studies and to compare the validity and reproducibility of LF with clinical visual examination (CVE) for the detection of occlusal caries under sealants. Three clinicians independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 42 publications
4
24
1
Order By: Relevance
“…These results disagree with those from Deery et al [2006], who showed lower LF measurements after sealing teeth stored in 1% aqueous thymol solution using the same material. This difference could be due to the method of storage.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These results disagree with those from Deery et al [2006], who showed lower LF measurements after sealing teeth stored in 1% aqueous thymol solution using the same material. This difference could be due to the method of storage.…”
Section: Discussioncontrasting
confidence: 99%
“…However, Anttonen et al [2003], in an in vivo study, and Krause et al [2008] reported that clear sealants did not affect LF measurements. Our results suggest that both devices could be used as an adjunct for caries diagnosis, as already suggested by Deery et al [2006] in relation to occlusal surfaces sealed with a clear sealant. The tendency of values to increase would not be clinically influential.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…[8][9][10][11] Previous studies have reported that fissure sealants do not affect LF readings. [12][13][14][15] However, other studies [16][17][18][19] have shown that the presence of sealants and composite filling materials might complicate the interpretation of the LF readings, leading to false-positive results.…”
Section: Introductionmentioning
confidence: 99%